Media, structures, and power : the Robert E. Babe collection - Babe, Robert E., 1943-; Comor, Edward A., 1962- (University of Toronto Press, 2011)
"Media, Structures, and Power is a collection of the scholarly writing of Canada's leading communication and media studies scholar, Robert E. Babe. Spanning almost four decades of scholarship, the volume reflects the breadth of Babe's work, from media and economics to communications history and political economy."--Pub. desc.